2017
DOI: 10.1002/oby.22061
|View full text |Cite
|
Sign up to set email alerts
|

Lithospermum erythrorhizon Root and its Naphthoquinones Repress SREBP1c and Activate PGC1α Through AMPKα

Abstract: Objective: To examine specific molecular mechanisms involved in modulating hepatic lipogenesis and mitochondria biogenesis signals by Lithospermum erythrorhizon (gromwell) root extract. Methods: Stable cell lines with luciferase reporter constructs were generated to examine sterol regulatory element binding protein 1c (SREBP1c) and peroxisome proliferator-activated receptor gamma, coactivator 1 (PGC1) a promoter activity and estrogen-related receptor (ERR) a response element activity. Gene expression of SREBP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A previous study by Duan [24] reported that calycosin, a major component of Astragali radix, ameliorates HFD-induced NAFLD by inhibiting gluconeogenesis through the modulation of Farnesoid X receptor (FXR) activation. In addition, shikonin, which is one of the naphthoquinones in LE, suppresses lipogenesis by increasing the phosphorylated AMPK in hepatocytes [30]. Based on these findings, we postulated that ALM16 would possess a certain level of cartilage protective effect and could exert multiple biological activities under various pathological conditions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous study by Duan [24] reported that calycosin, a major component of Astragali radix, ameliorates HFD-induced NAFLD by inhibiting gluconeogenesis through the modulation of Farnesoid X receptor (FXR) activation. In addition, shikonin, which is one of the naphthoquinones in LE, suppresses lipogenesis by increasing the phosphorylated AMPK in hepatocytes [30]. Based on these findings, we postulated that ALM16 would possess a certain level of cartilage protective effect and could exert multiple biological activities under various pathological conditions.…”
Section: Discussionmentioning
confidence: 95%
“…LE contains naphthoquinones, including shikonin and its derivatives, identified as the major phytochemicals [27]. Recent studies have reported the various biological activities of LE, including anti-inflammatory, antiobesity, and antilipogenic activities [28][29][30]. Especially, Gwon et al reported that ethanol extract of LE, which contains acetylshikonin as the main compound, exerted antiobesity effect through inhibition of lipogenic and adipogenic gene expression [29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AMPK, a phylogenetically conserved serine/threonine protein kinase, is an energy sensor that controls intracellular energy metabolism [ 36 ]. Once activated, AMPK is capable of inducing a series of biological activities for regulating the lipid metabolism, including the suppression of SREBP2 activation and upregulation of PGC-1 α [ 37 ]. In this study, the Western blot analysis indicated that HT administration obviously increased the activation of AMPK, suggesting that HT might activate AMPK to block the signal transduction of the downstream SREBP2/PCSK9 pathway, consequently resulting in the level reduction of blood LDL-C and alleviation of atherosclerosis development ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin, a naphthoquinone compound, is the primary active constituent of Zicao, which can be produced from the dried root of Lithospermum erythrorhizon (34). Shikonin has been reported to exert multiple pharmacological effects, including both anti-cancer and anti-inflammatory properties (35,36). However, the strong non-selective cytotoxicity of shikonin restricts its clinical application (36).…”
Section: Non-cytotoxic Doses Of Shikonin Inhibit Lipopolysaccharide-imentioning
confidence: 99%